Novice School Counselors’ Stress during COVID-19 Pandemic: A Qualitative Inquiry - Rahim Siti Nur Hazwani; Abu Bakar Abu Yazid; Salleh Amat; Suranata Kadek (Jurnal Bimbingan dan Konseling Indonesia, 2023)
This study was conducted to explore the causes and effects of stress among novice school counselors during the COVID-19 pandemic. This study employs a qualitative approach with combination data collection techniques of observation, interview and document analysis. The respondents involved six counselors who have just started their careers for less than one year in high school settings. The six respondents were sampled using the purposive sampling methodology. The main result of the study found that all respondents agreed that their feelings before taking up the position of a teacher and after becoming a teacher had many changes. It is also found that all respondents have a good understanding of the pressures and challenges they go through. Undoubtedly, it's critical for teachers to keep in mind that having personal experience may help them cope with stress.